(3efXheI aj Yde GdfMhs - (3YHO GdYRjR GdecfGSj GdaGSjs ((3CMeO Hf edG eMeO dGTGaYi GdMUcai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bO aVdG HGdYde bOeG NUge JaVdG hHYO aGdYde CLd eG CYJfi Hg GddHjH hgh fYe eG EbJfi s
(3BNQgG (B:s
(3hcdgG bO LeYJ ai GdHSedI aGdMeO ddg Ydi eG Ccedg JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda SfI (B951s
(3HgG NQe s
Keywords: (3GdeLGejYs